How do videos fit into current agricultural advisory services? Lessons from Kenya and Uganda - Aladesuru, Damilola T.; Kasule, James B.; Bosch, Christine; Kato, Edward; Ringler, Claudia; Birner, Regina (International Food Policy Research Institute, 2024)
While video extension is a recognized means to overcome the challenges posed by traditional agricultural advisory services, adoption has been limited. This paper presents two case studies conducted in Kenya and Uganda that explore the potential of video extension for promoting climate-smart agriculture (CSA) practices. In Kenya, videos were rolled out by GROOTS Kenya, which predominantly serves women farmers. In Uganda, the Ministry of Agriculture, Animal Industry and Fisheries’ Agricultural Extension Services implemented the video rollout, focusing on both women and men farmers. We used qualitative research linked to both video rollouts to understand the benefits and challenges linked to the intervention. We also compared the implementation strategies used in the two countries to evaluate the suitability of videos as a “best fit” advisory provision tool. Both women and men farmers enjoyed watching the videos. They improved farmers' access to information, resulting in increased knowledge and adoption of CSA practices. Costs involved in some practices affected their adoption as did lack of intrahousehold decision-making power, particularly for women. In some cases, infrastructural challenges complicated the video showings. The findings underscore the importance of complementing traditional agricultural extension with interactive and context-specific video content without replacing and neglecting other modes of extension, as well as the need for political support to ensure the scalability and long-term success of video extension initiatives.